Teori Grup Pada Algoritma DES Dan Transformasi Wavelet Diskrit Dalam Program Aplikasi Keamanan Citra Digital - Miftah Sigit Rahmawati; Rendra Soekarta (Insect (Informatics and Security): Jurnal Teknik Informatika, 2018)
Chryptography or Chriptology plays an important role in building data and information security. Chryptography aims to not read unauthorized people, so information can be safely maintained. Some research about Chryptography and algorithms related to data security have been done by practitioner of informatics and mathematic, one of which is DES algorithms and wavelet transform. DES algorithm is symmetrical standart algorithm which is widely used and is still considered safe to answer th challenges of the rapid development of information technology.This paper have discussed about application of Algebra in DES algorithms and discrete Wavelet Transform On Digital Image Security Application, i.e. XOR operation, permutation, andÂ  permutation group or siklik group which is used in DES algorithms on digital image security application. Then, as Group it found (x+b)-groupÂ  in discrete wavelet transform on digital image security application